Assessment of Noise Pollution Around Labuhan Ratu Railway Crossing: Implications for Health and Urban Development - Panggabean, Siti Munawarah; Tama, Dwi Sulis; Pawhestri, Suci Wulan; Andandaningrum, Della (ORGANISMS: JOURNAL OF BIOSCIENCES, 2024)
Noise pollution presents a serious challenge to community well-being, especially in rural areas, impacting health, technical functions, and psychological stability. This study aims to assess the level of noise pollution around the Labuhan Ratu railway crossing and analyze its impact on public health as well as urban development in the surrounding area. Using qualitative research methods, an exploratory survey was conducted with purposive sampling to measure disturbance intensity and its impacts. Results showed peak disturbance levels of 82.9 dB at a distance of 0-50 meters from the railway station, while the lowest disturbance measured was 55.7 dB at 100-150 meters. Both values are significantly above the SNI-03-6386-2000 threshold of 55 dB for community areas, indicating that the site is outside the standard. The findings highlight prevalent issues, including hearing impairment, communication difficulties, and psychological disorders among residents. Addressing these disturbances is crucial for improving community health and supporting SDG efforts to mitigate urban noise pollution, fostering a healthier living environment for affected populations, particularly in rural contextsAbstrakPolusi suara merupakan tantangan serius bagi kesejahteraan masyarakat, khususnya di daerah pedesaan, dengan dampak negatif terhadap kesehatan, fungsi teknis, dan stabilitas psikologis. Penelitian ini bertujuan untuk menilai tingkat polusi kebisingan di sekitar perlintasan kereta api Labuhan Ratu dan menganalisis dampaknya terhadap kesehatan masyarakat serta perkembangan perkotaan di sekitarnya. Penelitian menggunakan metode kualitatif melalui survei eksploratif dengan purposive sampling untuk mengukur intensitas kebisingan dan dampaknya. Hasil penelitian menunjukkan bahwa tingkat kebisingan tertinggi mencapai 82,9 dB pada jarak 0-50 meter dari stasiun, dan terendah 55,7 dB pada jarak 100-150 meter. Kedua tingkat kebisingan tersebut jauh melebihi ambang batas SNI-03-6386-2000 sebesar 55 dB untuk wilayah pemukiman, menunjukkan bahwa area tersebut berada di luar standar. Temuan ini mengungkapkan berbagai masalah yang dialami penduduk, seperti gangguan pendengaran, kesulitan komunikasi, dan gangguan psikologis. Penanganan masalah kebisingan ini penting untuk meningkatkan kesehatan masyarakat dan mendukung upaya SDGs dalam mengurangi polusi suara perkotaan, guna menciptakan lingkungan yang lebih sehat bagi masyarakat terdampak, terutama di daerah pedesaan